2014
DOI: 10.1002/mbo3.223
|View full text |Cite
|
Sign up to set email alerts
|

The E. coli sirtuin CobB shows no preference for enzymatic and nonenzymatic lysine acetylation substrate sites

Abstract: Nε-lysine acetylation is an abundant posttranslational modification of thousands of proteins involved in diverse cellular processes. In the model bacterium Escherichia coli, the ε-amino group of a lysine residue can be acetylated either catalytically by acetyl-coenzyme A (acCoA) and lysine acetyltransferases, or nonenzymatically by acetyl phosphate (acP). It is well known that catalytic acCoA-dependent Nε-lysine acetylation can be reversed by deacetylases. Here, we provide genetic, mass spectrometric, structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
113
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(121 citation statements)
references
References 69 publications
7
113
0
Order By: Relevance
“…These enzymes catalyse the transfer of an acetyl group from acetyl-CoA to the Nε-amino group of a lysine residue in a protein [14]. This form of acetylation can be reversible and in some cases irreversible [15], and is implicated as a regulatory mechanism that can potentially modulate protein–protein, DNA–protein, and other interactions. How RprY is activated by phosphorylation is still unclear, but the finding that the regulator is co-transcribed with a GNAT acetyltransferase prompted us to investigate whether RprY is acetylated in vivo and whether Pat activity is responsible.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These enzymes catalyse the transfer of an acetyl group from acetyl-CoA to the Nε-amino group of a lysine residue in a protein [14]. This form of acetylation can be reversible and in some cases irreversible [15], and is implicated as a regulatory mechanism that can potentially modulate protein–protein, DNA–protein, and other interactions. How RprY is activated by phosphorylation is still unclear, but the finding that the regulator is co-transcribed with a GNAT acetyltransferase prompted us to investigate whether RprY is acetylated in vivo and whether Pat activity is responsible.…”
Section: Resultsmentioning
confidence: 99%
“…The CobB deacetylase recognized autoacetylated RprY as a substrate, and in the presence of cofactor NAD + removed the modification (Figure 5(d)). A recent study showed that CobB did not deacetylate all acetyl-lysines in proteins whether derived enzymatically or non-enzymatically (autoacetylated) with Ac-CoA or AcP [15]. However, further analyses indicated that the most common CobB sensitive targets were metabolic enzymes and binding proteins, including those involved in DNA binding, transcription, and phosphorylated proteins [15,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this is the first evidence that the 30S ribosomal pro-tein S4 is acetylated and can be deacetylated by LpSirA, at least in Lactobacilli. AbouElfetouh et al (2015) have reported an extensive global analysis using cobB deletion mutant of E. coli and found 51 acetylated proteins in the bacterium. These proteins were sensitive to CobB and were involved primarily in translation, central metabolism and DNA-centered processes.…”
Section: Discussionmentioning
confidence: 99%
“…Protein acetyltransferases control the acetylation of specific proteins under various physiological conditions, whereas protein deacetylases play a role in removing the acetyl group from some acetylated proteins in response to changes in the cellular energy status via promptly sensing the intracellular NAD (NAD ϩ )-to-NADH ratio (5,7,18). In addition to deacetylating the proteins acetylated by acetyltransferases, protein deacetylases also specifically deacetylate the lysines acetylated by AcP (18).…”
Section: Microorganisms Have Developed Various Protein Posttranslatiomentioning
confidence: 99%